Understanding the form transformation of traditional towns and villages in China (1998-2021): a case study on the production of space in the cultural region of Huizhou - Cheng, Xiao (2022)
Not only Chinese cities have seen vast urban form transformations in the rapid urbanization process, the subordinate traditional towns and villages have also experienced profound form changes, but in a different mode compared to those in cities. This has been especially evident under waves of national policies promoting urbanization and rural development during the past two decades, such as ‘Urban Housing System Reform’, ‘New-Type Urbanization’, ‘Building a New Socialist Countryside’, ‘Construction of Beautiful Village’ and ‘Rural Revitalization’. However, in this process designers (e.g., planners, architects and urban designers) have embraced partial understandings of the form issues and offered problematic approaches to them. To more comprehensively understand the form transformation in traditional towns and villages beyond conventional planning and architectural design arena, deeper research is needed to explain the underlying social-spatial factors especially their logics, involving policy, economy, culture, capital, design, and local people’s ‘everyday life’ (Lefebvre, 1991a).